Early selection for spike fertility index increases yield of advanced generations in bread wheat - Alonso, María Pía; Franco, María Fiorella; Pontaroli, Ana Clara (Wiley, 2023)
Spike fertility index (a.k.a. fruiting efficiency) at maturity (FEm -grain number per spike/g spike chaff at maturity-) and spike harvest index (SHI -grain weight per spike/g spike chaff weight at maturity-) are considered promising selection criteria for improving grain yield (GY) in bread wheat. However, their usefulness in early generations remains to be established. Here, a population derived from a cross between ‘Baguette 10′ and ‘Klein Chajá’ was evaluated from early generations (F2-F3) to recombinant inbred lines (RIL). Associations of FEm and SHI measurements between early generations and RIL were established. Also, responses in grain number/m2 (GN) and GY in the RIL after simulated selection for high FEm or high SHI in the F2-F3 were assessed. Positive correlations were found in FEm measured in the F2-F3 vs. in the RIL (r = 0.32, P < 0.05) and SHI measured in the F3 vs. in the RIL (r = 0.26, P < 0.05). After selection for high FEm in the F2-F3, responses in GN were always positive: GN increased by 5.1 to 22.1% depending on the selection strategy. Responses in GY were positive in three out of four selection strategies, averaging -1.3 to 2.1%. Responses to selection in GN and GY in the RIL using SHI as a selection criterion in the F2-F3 were negative or neutral. Our results support the use of FEm as a selection criterion in early generations for increasing GN and GY in advanced generations of bread wheat breeding programs.